A method for preparing titanium-titanium composite double-layer blank by diffusion bonding process

Connecting titanium ingots through vacuum diffusion connection technology solves the problem of lack of effective processes in the prior art to prepare titanium-titanium composite plates, and achieves the preparation of titanium-titanium composite materials with high binding strength and low cost.

CN115722785BActive Publication Date: 2025-04-11KUNMING UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211580761.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-10
Publication Date
2025-04-11
Estimated Expiration
2042-12-10

AI Technical Summary

Technical Problem

The lack of effective process methods in the prior art to prepare titanium-titanium composite panels has resulted in limited application in the field of composite materials.

Method used

Different titanium ingots are connected by vacuum diffusion connection technology, and diffusion pressure is applied through surface grinding and polishing, and segmented heating and insulation are carried out in a vacuum furnace to achieve the preparation of titanium-titanium composite double-layer blank.

Benefits of technology

The process is simple, convenient to operate, low cost, no burn-out on the outside, high binding strength and good composite control rate. The combined strength of the prepared titanium-titanium composite ingot can reach more than 80% of the base material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115722785B_ABST
    Figure CN115722785B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a titanium-titanium composite double-layer billet by a diffusion bonding process. The method of the present invention adopts a titanium ingot whose surface has been cleaned, and the polished surface and the opposite surface of the titanium ingot are combined and placed in a vacuum furnace, and then diffusion pressure is applied; then the vacuum furnace is closed and evacuated, and when the vacuum degree is lower than 10 ‑3 Pa, adopt segmented heating, wait until the temperature required for diffusion, start diffusion bonding, stop heating after a certain period of diffusion bonding, cool with the furnace, and maintain vacuum during the cooling process. The titanium-titanium double-layer blank prepared by the method of the present invention has the characteristics of simple operation, low cost, no burning loss on the outer surface, high bonding strength, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium-titanium composite double-layer blank by a diffusion bonding process, belonging to the technical field of metal composite material preparation. Background Art

[0002] With the continuous development of society, different materials are needed in all walks of life. Titanium alloy is a non-ferrous metal. In the past, due to the limited smelting and processing technology, the high cost of titanium and its products made it impossible to produce and use them on a large scale. Through the efforts of scientists, great breakthroughs have been made in related fields, but a single variety of titanium or titanium alloy cannot meet the needs of industrial production, so the composite titanium material industry has been born. Because of the emergence of this material, the application of titanium materials can be greatly promoted and its scope of use can be expanded.

[0003] Titanium is an extremely active metal that easily absorbs oxygen at high temperatures, which reduces the strength of the joint. According to the needs of the project, titanium or titanium alloys will be compounded to give the titanium material the characteristics of two titanium alloys to meet the needs of the work. In some specific cases, such as when both light weight and high strength need to be considered, a single metal cannot meet the needs, and it is necessary to select a suitable alloy according to the requirements of different parts.

[0004] At present, a large number of domestic patents on titanium alloy composite plates are concentrated on titanium-steel, titanium-aluminum, titanium-magnesium, titanium-copper and other composite plates; while there are fewer related patents on titanium-titanium composite plates.

[0005] Patent authorization announcement number (CN101092710B), the patent introduces a method for preparing a titanium-copper composite plate. The invention uses one or more of welding, rolling and hot pressing processes to prepare a titanium-copper composite plate in which the titanium completely or partially covers the copper plate.

[0006] Patent authorization announcement number (CN108114980A), the patent introduces a method for preparing titanium-magnesium composite plates by electromagnetic induction heating and different temperature straight rolling. The invention provides a method for preparing titanium-magnesium composite plates by electromagnetic induction heating and different temperature straight rolling. Using ferromagnetic materials, the thermal effect generated by eddy current heating can rapidly increase the temperature of the iron plate, which is then transferred to the titanium plate and the magnesium plate in turn. Under the premise of low energy consumption, electromagnetic induction heating is used to quickly form a temperature difference between the titanium and magnesium plates, thereby reducing the difference in deformation resistance between the plates to achieve coordinated deformation, and symmetrical rolling is achieved under different temperature conditions, resulting in a titanium-magnesium composite plate with good flatness.

[0007] Patent authorization announcement number (CN114393036A). Compared with the traditional rolling method, the preparation method of the titanium-aluminum composite plate provided by the invention has a simplified process, a simple process, is easy to operate, and is suitable for large-scale industrial production; the titanium-aluminum composite plate prepared by the method of the invention has excellent interface bonding strength, good plate shape, and high yield rate, which can effectively solve the problem of the relatively complicated process of the existing titanium-aluminum composite plate preparation method.

[0008] Patent authorization announcement number (CN115007989A), the invention uses explosive composite method to successfully prepare ultra-thin large-size titanium steel metal composite plates for ships; the thickness of the titanium plate is 0.5mm~2mm, the length of the titanium plate and the steel plate is 8000mm~10000mm, and the thickness of the steel plate is ≥10mm.

[0009] Patent authorization announcement number (CN115319264A), the invention uses explosive composite method to successfully prepare a three-layer structure titanium alloy composite plate; the interface between the titanium plates is well bonded, the corrosion resistance at different positions of the composite plate is good, and the mechanical properties are excellent.

[0010] In summary, it can be seen that the existing domestic production technology has not yet found a process method for compounding titanium-titanium billets using vacuum technology. Therefore, the method provided by the present invention can lay a good foundation for future industrial development. Summary of the invention

[0011] In view of the lack of relevant manufacturing process of titanium-titanium composite plates in the above-mentioned existing composite plate field, the purpose of the present invention is to provide a method for connecting different titanium ingots by vacuum diffusion connection, which has the advantages of simple process, convenient operation, low cost, no burn damage on the surface, high bonding strength and good composite control rate.

[0012] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0013] A method for preparing a titanium-titanium composite double-layer blank by a diffusion bonding process, specifically comprising the following steps:

[0014] (1) The titanium ingot is washed to expose the metallic luster on the surface, then polished with sandpaper, and finally polished with polishing paste until the surface of the titanium ingot is mirror-like. The polished sample is dried under vacuum conditions, covered with a protective film to isolate oxidation, and set aside.

[0015] (2) Place the polished surface of the titanium ingot on the opposite side and apply diffusion pressure. The pressure is applied in the following manner: Figure 1 or Figure 2 .

[0016] (3) Close the cover of the vacuum furnace and start to evacuate the furnace. The vacuum degree is less than 10 -3 When the thickness is 0.04mm, the temperature is 0.04mm / s and the thickness is 0.08mm. When the thickness is 0.04mm / s, the temperature is 0.08mm / s and the temperature is 0.08mm / s. When the temperature is 0.08mm / s, the temperature is 0.08mm / s and the temperature is 0.08mm / s ... temperature is 0.08mm / s, the temperature is 0.08mm / s and the temperature is 0.08mm / s.

[0017] H=0.13×t

[0018] H is the thickness of the titanium ingot in mm, 0.13 is the empirical heating coefficient, and t is the diffusion time in min.

[0019] (4) When the diffusion bonding is completed, stop heating and cool in the furnace, and maintain the vacuum during the cooling process.

[0020] (5) During the cooling process, air can only be introduced when the temperature drops below 200°C.

[0021] (6) The diffusion strength between titanium composite ingots is determined by the type of titanium alloy; the currently connected titanium ingots are mainly TA and TC, TA and TA, and their bonding strength can reach 60% of the lower tensile strength of the parent material.

[0022] Preferably, in step (1) of the present invention, the sandpaper is selected from coarse to fine, and the specific sandpaper mesh is 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, 1800#, 2000#; and diamond polishing paste is used for polishing, and the particle sizes are 1 μm, 0.5 μm, 0.1 μm, and 0.05 μm, respectively.

[0023] Preferably, the polished sample in step (1) of the present invention is dried at a temperature of 80° C. for 2 hours.

[0024] Preferably, the diffusion pressure is applied in step (2) of the present invention as follows: in a hood-type vacuum furnace, the polished surfaces of the titanium ingots are placed on top of the opposite surfaces, and the required pressure of the titanium ingots is achieved by adding relevant counterweights to the upper titanium ingots; copper foil or aluminum foil can be added as an intermediate layer between the titanium ingots as needed to increase the connection effect. If no copper foil or aluminum foil is added, the required pressure will be greater.

[0025] Preferably, the pressure range required for the composite of TA (αTi) and TA titanium ingots of the present invention is 6-8 MPa; the pressure range required for the composite of TA and TC (α+β titanium) titanium ingots is 5-9 MPa.

[0026] Preferably, the temperature range required for the composite of TA and TA titanium ingots of the present invention is 830-880°C; and the temperature required for the composite of TA and TC titanium ingots is 870-950°C.

[0027] Preferably, when diffusion bonding is used for TA and TA ingots of the present invention, the diffusion time is 3-4 hours, and when diffusion bonding is used for TA and TC ingots, the diffusion time is 2-4 hours.

[0028] Compared with the prior art, the present invention has the following beneficial effects: the equipment required by the present invention is a vacuum furnace, and compared with explosive compounding, no dedicated explosion site is required; compared with explosive connection, the noise caused by diffusion connection will be greatly reduced; compared with explosive connection, the diffusion connection process can also arbitrarily select the sample size.

[0029] The present invention adopts a diffusion bonding process to compositely connect TA and TC titanium alloy ingots; a hood-type vacuum furnace is used to perform diffusion bonding to prepare titanium-titanium composite ingots; the prepared titanium-titanium composite ingots have a bonding strength of more than 80% of the parent material; the process is simple to operate and does not require the investment of new equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the method of increasing the pressure of the titanium ingot assembly of the present invention by fixing it with steel bars;

[0031] Figure 2 It is a schematic diagram of applying pressure to a titanium-titanium composite ingot by means of a counterweight;

[0032] Figure 3 It is a schematic diagram of the composite billet in a bell-type vacuum furnace;

[0033] Figure 4 is a macroscopic schematic diagram of Example 1;

[0034] Figure 5 is a schematic diagram of the bonding interface of Example 2;

[0035] Figure 6 This is a schematic diagram of the organizational morphology at the bonding interface of Example 3.

[0036] Reference numerals: Figure 1 1 is a titanium material; 2 is another titanium material; 3 is a fixed steel belt;

[0037] Figure 2 No. 4 in the middle is a counterweight; No. 1 is a titanium material; No. 2 is another titanium material;

[0038] Figure 3 No. 5 in the middle is the vacuum furnace cover, No. 6 is the combined titanium ingot, and No. 7 is the vacuum furnace stage. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but the protection scope of the present invention is not limited to the contents shown.

[0040] In this embodiment, two different titanium ingots are made of a crystallizer of the same size. According to the size of the hearth of the bell-type vacuum furnace, a rectangular crystallizer is preferably used to increase the utilization rate of the furnace. The specific size of the diffusion connection sample is 2000*1200*210mm.

[0041] Example 1

[0042] (1) Select industrial pure titanium TA2 and TA1 titanium ingots, the size of which is 1200*210 mm and the length is between 8 and 10 m; cut them into rectangles with a length of 2 m by a sawing machine; and then use a vacuum drying furnace to dry the surface to provide a basis for the diffusion connection of the titanium ingots in the next step.

[0043] (2) The surface of the titanium ingot is rough and cannot be directly diffused and bonded, so it needs to be polished. The titanium ingot is cut into the size of the first step and milled on a milling machine to expose the metallic luster on the surface of the titanium ingot. The surface of the titanium ingot that needs to be diffused and bonded is then polished with sandpaper from coarse to fine. The specific sandpaper mesh is 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, 1800#, 2000#. It is then polished with polishing paste until the surface of the titanium ingot is mirror-like. Diamond polishing paste is used, and the particle sizes are 1 μm, 0.5 μm, 0.1 μm, and 0.05 μm, respectively.

[0044] (3) Place the polished sample in a drying oven for drying to remove the residual water vapor on the surface of the titanium ingot, and place it in a vacuum drying furnace at a temperature of 80°C for 2 hours; after cooling to room temperature, seal the surface that needs to be diffused.

[0045] (4) Aluminum foil is directly added to the titanium ingot as an intermediate layer to apply diffusion pressure. According to the pressure required by the titanium ingot, the required pressure is achieved by adding relevant counterweights to the upper titanium ingot. The pressure required for diffusion is 7 MPa. The combination method is as follows: Figure 3 shown.

[0046] (5) Close the cover of the vacuum furnace and start evacuating the furnace until the vacuum degree reaches less than 10 -3 Pa, set the diffusion temperature. Generally, segmented heating is used with a heating rate of 20℃ / min. Heat to 600℃, keep warm for 1.5 hours, and then continue to heat to 850℃ for diffusion bonding. The insulation time is 4h. Finally, heat to the temperature required for diffusion and start diffusion bonding.

[0047] (6) When the diffusion bonding is completed, the heating is stopped and the ingot is cooled in the furnace. After the temperature of the titanium ingot is cooled to below 100°C, the furnace is opened and the composite ingot is taken out. The vacuum is still maintained during the cooling process. The influence of the diffusion temperature on the performance of the interface connection is shown in Table 1 below.

[0048] Table 1

[0049] Temperature / ℃ 850 880 920 Tensile strength / MPa 157 134 112

[0050] Titanium ingot assembly Figure 1 As shown; the composite blank is placed as Figure 2 As shown; the macroscopic morphology of the plate is as Figure 4 As shown, combined Figure 4 It can be seen from Table 1 that as the diffusion temperature increases, the bonding strength decreases. This is because as the temperature of the diffusion interface increases, the content of intermetallic compounds at the interface increases, thereby reducing the bonding strength of the diffusion interface.

[0051] Example 2

[0052] (1) Select TA2 and TC4 titanium ingots, the titanium ingots are 1200*210 mm and the length is between 8-10 m; cut into rectangles with a length of 2 m by a sawing machine; and then use a vacuum drying furnace to dry the surface to provide a basis for the diffusion connection of the titanium ingots in the next step.

[0053] (2) The surface of the titanium ingot is rough and cannot be directly diffused and bonded, so it needs to be polished. The titanium ingot is cut into the size of the first step and milled on a milling machine to expose the metallic luster on the surface of the titanium ingot. The surface of the titanium ingot that needs to be diffused and bonded is then polished with sandpaper from coarse to fine. The specific sandpaper mesh is 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, 1800#, 2000#. It is then polished with polishing paste until the surface of the titanium ingot is mirror-like. Diamond polishing paste is used, and the particle sizes are 1μm, 0.5μm, 0.1μm, and 0.05μm, respectively.

[0054] (3) Place the polished sample in a drying oven for drying to remove the residual water vapor on the surface of the titanium ingot, and place it in a vacuum drying furnace at a temperature of 80°C for 2 hours; after cooling to room temperature, seal the surface that needs to be diffused.

[0055] (4) Apply diffusion pressure. According to the pressure required by the titanium ingot, copper foil is added as the intermediate connection layer. The required pressure is achieved by adding relevant counterweights to the upper titanium ingot. The pressure required for diffusion is 9 MPa. The combination is as follows: Figure 3 shown.

[0056] (5) Close the cover of the vacuum furnace and start evacuating the furnace until the vacuum degree reaches less than 10 -3 Pa, set the diffusion temperature. Generally, segmented heating is used with a heating rate of 20℃ / min. Heat to 600℃, keep warm for 2 hours, and then continue to heat to 920℃ for diffusion connection. The holding time is 2h. Finally, heat to the temperature required for diffusion and start diffusion connection.

[0057] (6) When the diffusion bonding is completed, the heating is stopped and the ingot is cooled in the furnace. After the temperature of the titanium ingot is cooled to below 100°C, the furnace is opened and the composite ingot is taken out. The vacuum is still maintained during the cooling process. The influence of the diffusion time on the performance of the interface connection is shown in Table 2 below.

[0058] Table 2

[0059] time 1h 2h 3h tensile strength 357MPa 543MPa 512MPa

[0060] Titanium ingot assembly Figure 1 As shown, the composite blank is placed as Figure 2 As shown; the interface morphology of the plate is as Figure 5 It can be seen from the figure that the interface is well bonded, and the tensile strength of the composite ingot increases with the increase of diffusion time. This is because diffusion takes time. Within the diffusion time of 1h, the interface is not completely fused, resulting in a decrease in bonding strength. If the diffusion time is continued to increase, the interface will be completely fused and the tensile strength will reach the maximum. If heating is continued, the intermetallic compounds generated at the interface will cause the interface strength to decrease.

[0061] Example 3

[0062] (1) Select TA10 and TC4 titanium ingots, the titanium ingots are 1200*210 mm in size and 8-10 m in length; cut into rectangular pieces with a length of 2 m by a sawing machine; and then use a vacuum drying furnace to dry the surface to provide a basis for the diffusion connection of the titanium ingots in the next step.

[0063] (2) The surface of the titanium ingot is rough and cannot be directly diffused and bonded, so it needs to be polished. The titanium ingot is cut into the size of the first step and milled on a milling machine to expose the metallic luster on the surface of the titanium ingot. The surface of the titanium ingot that needs to be diffused and bonded is then polished with sandpaper from coarse to fine. The specific sandpaper mesh is 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, 1800#, 2000#. It is then polished with polishing paste until the surface of the titanium ingot is mirror-like. Diamond polishing paste is used, and the particle sizes are 1 μm, 0.5 μm, 0.1 μm, and 0.05 μm, respectively.

[0064] (3) Place the polished sample in a drying oven for drying to remove the residual water vapor on the surface of the titanium ingot, and place it in a vacuum drying furnace at a temperature of 80°C for 2 hours; after cooling to room temperature, seal the surface that needs to be diffused.

[0065] (4) Apply diffusion pressure. According to the pressure required by the titanium ingot, copper foil is added as the intermediate connection layer. The required pressure is achieved by adding relevant weights to the upper titanium ingot. The pressure required for diffusion is 5 MPa. The combination is as follows: Figure 3 shown.

[0066] (5) Close the cover of the vacuum furnace and start evacuating the furnace until the vacuum degree reaches less than 10 -3 Pa, set the diffusion temperature, generally use segmented heating, heating temperature rate is 20 ℃ / min, heat to 800 ℃, then keep warm for 3 hours, and then continue to heat to 900 ℃, diffusion bonding, the insulation time is 1h; finally heat to the temperature required for diffusion, start diffusion bonding.

[0067] (6) When the diffusion bonding is completed, the heating is stopped and the ingot is cooled in the furnace. After the temperature of the titanium ingot is cooled to below 100°C, the furnace is opened and the composite ingot is taken out. The vacuum is still maintained during the cooling process. The influence of the diffusion pressure on the performance of the interface connection is shown in Table 3 below.

[0068] Table 3

[0069] pressure 3MPa 4MPa 5MPa tensile strength 462MPa 512MPa 524MPa

[0070] Titanium ingot assembly Figure 1 As shown, the composite blank is placed as Figure 2 As shown; the interface morphology of the plate is as Figure 6 ,It can be seen from Table 3 that the bonding strength increases with the increase of pressure. This is because pressure can provide greater activation energy. However, when the pressure continues to increase, the parent material will soften and cannot provide more activation energy, so the tensile strength does not change much.

Claims

1. A method for preparing a titanium-titanium composite double-layer blank by a diffusion bonding process, characterized in that: The specific steps include: (1) The titanium ingot is washed to expose the metallic luster on the surface, then polished with sandpaper, and finally polished with polishing paste until the surface of the titanium ingot is mirror-like. The polished sample is dried under vacuum conditions, covered with a protective film to isolate oxidation, and set aside; (2) Place the polished surfaces of the titanium ingots opposite to each other and apply diffusion pressure; (3) Close the cover of the vacuum furnace and start to evacuate the furnace until the vacuum degree reaches less than 10 -3 Pa, heating begins, and the heating method is segmented heating, the heating temperature rate is 20℃ / min, heated to 600℃, then kept warm for 1.5 hours, and then continued to heat to 800℃, kept warm for 1.5 hours; finally heated to the temperature required for diffusion, and started diffusion bonding. The heating time is related to the thickness, and the relationship is as follows: ; in, H is the thickness of the titanium ingot, mm; 0.13 is the empirical heating coefficient; t is the diffusion time, min; (4) When the diffusion bonding is completed, stop heating and use furnace cooling to cool the steel sheet, and maintain the above-mentioned vacuum degree during the furnace cooling process; The diffusion pressure is applied in step (2) by placing the polished surface of the titanium ingot and the opposite surface of the titanium ingot on the stage of the bell-type vacuum furnace, and according to the required pressure of the titanium ingot, the required pressure is achieved by adding relevant counterweights to the upper titanium ingot; Copper foil or aluminum foil can be added between titanium ingots as an intermediate layer as needed; When TA and TA are connected, the pressure range required for the composite of TA and TA titanium ingots is 6-8MPa; when TA and TC are connected, the pressure range required for the composite of TA and TC titanium ingots is 5-9MPa; The temperature range required for the composite of TA and TA titanium ingots is 830-880℃; for the composite of TA and TC titanium ingots, the temperature required is 870-950℃; The diffusion time of TA and TA ingots is 3-4 hours when diffusion bonding is used, and the diffusion time of TA and TC ingots is 2-4 hours when diffusion bonding is used.

2. The method for preparing a titanium-titanium composite double-layer billet by the diffusion bonding process according to claim 1, characterized in that: In step (1), the sandpaper is selected from coarse to fine, and the specific grits of the sandpaper are 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, 1800#, and 2000#; the polishing agent is diamond polishing paste, and the particle sizes are 1 μm, 0.5 μm, 0.1 μm, and 0.05 μm, respectively.

3. The method for preparing a titanium-titanium composite double-layer billet by the diffusion bonding process according to claim 1, characterized in that: The polished sample in step (1) is dried at 80°C for 2 h.

Citation Information

Patent Citations

  • Production method of composite board of titanium / copper

    CN101092710B

  • Method for preparing titanium-magnesium composite plate by electromagnetic induction heating and different-temperature straight rolling

    CN108114980A

  • Preparation method of titanium-aluminum composite plate

    CN114393036A

  • Marine ultrathin large-specification titanium steel metal composite plate and preparation method thereof

    CN115007989A

  • Preparation method of titanium alloy strong / plastic / tough layered composite plate

    CN115319264A